ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH - Handayani, Juli (UNPERBA, 2023)
The purpose of the study was to find out how the influence of tangibles, reliability, responsiveness, assurance and empathy variables on customer satisfaction. This type of research is quantitave with accidental sampling techniques and quantitative analysis techiiques with multiple linear regression. The results showed that the variables of tangibles, reliability, responsiveness, assurance, and empathy simultaneously or jointly affect the level of customer satisfaction. This is indicated by F count>F table, namely 29,834>2,20 or the Sig value F (0,000) < a = 0,05, the result is significant. Partially the variables that have a positive and significant effect are tangibles, reliability, assurance and empathy. Responsiveness varibles have a positive but not signisficant effect. The variables that have most dominant effect are empathy variables.